"Aisatsu" in Japanese Language Education - et. al., Uning Kuraesin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In Japanese society the aisatsu culture is very important. This is done with the aim of establishing a good relationship between humans. Through Aisatsu, communication will be fostered, so that social relations with others, both in a personal environment and in work relationships will be well established.In this paper, the author tries to see as an early study the use of aisatsu in communication in a formal environment. Formal aisatsu is commonly used in campus life from a learner to his teacher, or in subordinate-superior relationships in a work environment.Aisatsu in Japanese, not only serves as an ordinary greeting in everyday life, but in a higher context, such as communication in business, aisatsu can be used as a tool in running its business. By doing aisatsu, there are many meanings contained in it, both as an expression of praise, respect, encouragement, ect.In this paper, the author tries to describe the ways in which some aisatsu are used in Japanese and the discrepancies that often arise in Japanese learners. Such as the use of aisatsu, 「お は よ う ご ざ い ま す」 「こ ん に ち は」 「お め で と うご ざ い ま す」, etc. In the context of communication, the use of aisatsu is highly influenced by culture. Thus, the use of aisatsu in formal situations is not appropriate to use.